PEMANFAATAN INSTAGRAM OLEH GENERASI MILENIAL SEBAGAI MEDIA BISNIS ONLINE DI KOTA BATAM - AYU ANDIRA RASYID,; ANGEL PURWANTI, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Instagram is currently more widely used to promote business by an entrepreneur. The development of technology is currently used by business people to promote and develpo their business quickly and widely by using online applications, especially instagram. The purpose of this is to know the use of instagram as an online business media for millennial generations in Batam. This type of research uses descriptive qualitative method. The sample used was obtained by purposive sampling technique. Data collection techniques can be done by observation, in-depth interviews, and literature study from various sources of research material. The results of this study indicate that instagram is used by entrepreneur as a business promotion and can increase sales from before.